The Cytochrome P450-Mediated Metabolism Alternation of Four Effective Lignans From Schisandra chinensis in Carbon Tetrachloride-Intoxicated Rats and Patients With Advanced Hepatocellular Carcinoma - Rongrong Wu; Rongrong Wu; Zhiyong Xiao; Xiaorui Zhang; Feng Liu; Wenxia Zhou; Yongxiang Zhang (Frontiers Media S.A., 2018)
It is highly valuable to study the pharmacokinetics of herbal components under the pathological condition of liver dysfunction for safe and rational use of herbal medicines. In this study, the pharmacokinetic profiles of four effective lignans from Schisandra chinensis (SC), schisandrin, schisantherin A, deoxyshisandrin and γ-schisandrin, were investigated in carbon tetrachloride (CCl4)-intoxicated rats. The metabolism of the four lignans was also studied using microsomes from patients with advanced hepatocellular carcinoma. In situ intestinal and hepatic perfusions were conducted to clarify the contributions from impairments of gut and liver on the pharmacokinetics of the four schisandra lignans in CCl4-intoxicated rats. The metabolism in rat and human liver microsomes and transport in Caco-2 monolayer cell model were studied to reveal the key factors for the in vivo disposition of the four lignans. When SC alcoholic extract was orally administrated to CCl4-intoxicated rat for a short term (4 days), the pharmacokinetics of four active SC lignans was significantly changed while its hepatotherapeutic effect was not obviously observed. The plasma concentrations of the four schisandra lignans were dramatically elevated compared with the control. The Cmax, AUC and MRT were all increased or prolonged significantly while parameter CLz/F was obviously reduced in rat pretreated with CCl4. In hepatic perfusion study and liver microsomes incubation, it was found that the hepatic metabolism of the four lignans was markedly decreased mainly due to the activity reduction of multiple CYP450 isoenzymes involved the metabolism, which, eventually, might lead to the alternation of their pharmacokinetic profiles in CCl4-intoxicated rats or patients with advanced hepatocellular carcinoma. The pharmacokinetic studies of SC components in pathological situation of liver dysfunction are expected to provide useful data for rational and safe application of SC preparations in clinic or further pharmacological and toxicological research.